Quantitation of cannabinoid CB1 receptors in healthy human brain using positron emission tomography and an inverse agonist radioligand - Terry, Garth E.; Liow, Jeih-San; Zoghbi, Sami S.; Hirvonen, Jussi; Farris, Amanda G.; Lerner, Alicja; Tauscher, Johannes T.; Schaus, John M.; Phebus, Lee; Felder, Christian C.; Morse, Cheryl L.; Hong, Jinsoo S.; et al. (NeuroImage (Orlando, Fla.), 2009)
[11C]MePPEP is a high affinity, CB1 receptor-selective, inverse agonist that has been studied in rodents and monkeys. We examined the ability of [11C]MePPEP to quantify CB1 receptors in human brain as distribution volume calculated with the “gold standard” method of compartmental modeling and compared results with the simple measure of brain uptake. A total of 17 healthy subjects participated in 26 positron emission tomography (PET) scans, with 8 having two PET scans to assess retest variability. After injection of [11C]MePPEP, brain uptake of radioactivity was high (e.g., 3.6 SUV in putamen at ∼60 min) and washed out very slowly. A two-tissue compartment model yielded values of distribution volume (which is proportional to receptor density) that were both well identified (SE 5%) and stable between 60 and 210 min. The simple measure of brain uptake (average concentration of radioactivity between 40 and 80 min) had good retest variability (∼8%) and moderate intersubject variability (16%, coefficient of variation). In contrast, distribution volume had two-fold greater retest variability (∼15%) and, thus, less precision. In addition, distribution volume had three-fold greater intersubject variability (∼52%). The decreased precision of distribution volume compared to brain uptake was likely due to the slow washout of radioactivity from brain and to noise in measurements of the low concentrations of [11C]MePPEP in plasma. These results suggest that brain uptake can be used for within subject studies (e.g., to measure receptor occupancy by medications) but that distribution volume remains the gold standard for accurate measurements between groups.